Evaluasi realisasi pencapaian target pajak daerah untuk penerimaan pajak daerah tahun 2020-2023 pada Badan Pendapatan Daerah Kota Manado - Tulungen, Yosua Satrianly; Warongan, Jessy D. L.; Mintalangi, Syermi S. E. (Yayasan Widyantara Nawasena Raharja, 2024)
Taxes are one of the most potential resources and the largest contributor in maximizing regional revenue. Therefore, the government continues to try and strive to increase Regional Original Revenue (PAD) sourced from the regional tax sector. The purpose of the study is to find out the realization of the achievement of the regional tax target for regional tax revenue in 2020 - 2023 at the Regional Revenue Agency of Manado City. The analysis method used in this study is qualitative descriptive analysis. In this study, data on the realization of the tax revenue budget for regional taxes in 2020-2023 collected by the Manado City Regional Revenue Agency was used. The results of this study show that the realization of regional tax revenues for 2020 – 2023 has not yet reached the target because there are still many regional tax potentials that have not been explored. This condition is also supported by non-technical problems such as technological developments, the ineffectiveness of online tax collection applications or systems and the existence of large-scale social restrictions during the COVID-19 pandemic and also the low awareness of taxpayers in carrying out tax obligations greatly affects regional tax revenues so that the Manado City Regional Revenue Agency continues to strive to optimize regional tax collection. The efforts made by the Manado City Regional Revenue Agency to overcome problems in regional tax collection are efforts to intensify and extensify regional taxes. The results of this study show that the realization of the achievement of regional tax revenue targets in Manado City has not been optimal due to the impact of the Covid-19 pandemic so that tax collection has not been maximized which results in the non-achievement of the set target. There is only one type of regional tax that reaches the target, namely restaurant taxes in 2022-2023.